ANALISIS YURIDIS TINDAK PIDANA PEMILU DENGAN SENGAJA MENYEBABKAN ORANG LAIN KEHILANGAN HAK PILIHNYA: JURIDICAL ANALYSIS OF ELECTION CRIMINAL ACTS INTENTIONALLY CAUSED OTHERS TO LOSE THEIR VOTIONAL RIGHTS - Dwi Handoyo, Nanda; Almusawir; Rusli, Muhammad (Clavia, 2021)
This study was intended to find out what factors caused the defendant to commit an election crime in a court ruling number: 973 / Pid.Sus / 2019 / Pn Mksr who had permanent legal force (Inkracht Van Gwijsde), and to find out what was considered by the judge. in imposing criminal sanctions on the defendant. The research method that the author uses is USING primary and secondary data sources through communication / interview techniques and libraries by analyzing data received from juridical normative then concluded descriptively by describing, explained and elaborating about the implementation of law enforcement. The defendant's actions cannot be seen as mere acts of violation of the law, but they have also violated democracy held on the basis of direct, public, free, secret, honest and fair. From the results of research and discussion shows that the factors causing the defendant to commit an election crime are that the defendant removes the voting rights of others by giving citizens invitations to his two grandchildren on the grounds that his grandson does not want to abstain in the 2019 election and the defendant recognizes the act. In their verdict, the judge considered that sanctions were imposed according to the defendant. The judge has acted wisely and discerning by seeing the circumstances that were alleviating and also against the defendant.